High-gain and low-profile antenna using novel reflective surface for satellite applications - Lan Ngoc Nguyen (PLoS ONE, 2026)
A low-profile and compact antenna that offers wideband and high-gain features for satellite applications is investigated in this work. Instead of using an AMC surface for enhancing gain as in conventional antenna designs, this paper proposes a reflective surface made of pure copper laminate, and the results exhibit a 5 dB gain enhancement. In addition, the broadband performance is realized by loading partial ground technique. As a result, only four patch elements, the antenna designed at the central frequency of 4.3 GHz exhibits a bandwidth of 21.4% at −10 dB, a peak gain of 14 dBi and an efficiency over 80% over the frequency range of operating. The design concept is validated through measurements conducted on a fabricated prototype. In addition, the performance of the proposed antenna is compared with existing literature in order to highlight the importance of the proposed work.